2014
DOI: 10.1051/0004-6361/201323311
|View full text |Cite
|
Sign up to set email alerts
|

Fossil group origins

Abstract: Aims. This study is part of the Fossil group origins (FOGO) project which aims to carry out a systematic and multiwavelength study of a large sample of fossil systems. Here we focus on the relation between the optical luminosity (L opt ) and X-ray luminosity (L X ). Methods. Out of a total sample of 28 candidate fossil systems, we consider a sample of 12 systems whose fossil classification has been confirmed by a companion study. They are compared with the complementary sample of 16 systems whose fossil nature… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 62 publications
(63 reference statements)
2
54
0
Order By: Relevance
“…We used an iterative procedure based on PIMMS 5 (Mukai 1993). Details of the procedure are available in Girardi et al (2014).…”
Section: Cluster Global Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…We used an iterative procedure based on PIMMS 5 (Mukai 1993). Details of the procedure are available in Girardi et al (2014).…”
Section: Cluster Global Propertiesmentioning
confidence: 99%
“…Thus, uncertainties in the R 200 determination reflect in uncertainties in the fossil classification. Therefore, we computed the variation in the number of fossil systems considering a 25% uncertainty in R 200 in agreement with Girardi et al (2014). The number of fossil systems is 15 +8 −4 .…”
Section: Fossilness Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences between FS and non-FS were also reported in scaling relations combining optical and X-ray quantities, such as the L X − L opt or L X − σ relations (e.g., Proctor et al 2011;Khosroshahi et al 2014); they were interpreted as an indication that the halos of FSs formed early in the high redshift Universe. Nevertheless, larger samples of FSs and non-FSs have obtained that those differences do not exist, indicating that according to the global scaling relations, fossil and non-fossil halos are similar (e.g., Harrison et al 2012;Girardi et al 2014;Kundert et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, these differences can be attributed to observational biases (see Voevodkin et al 2010;Harrison et al 2012). Recently, Girardi et al (2014) have analyzed a sample of 15 spectroscopically confirmed FGs, finding no significant differences in the L X − L opt relation. Particular attention was paid to the homogeneity of the data set and the analysis process in this work.…”
Section: Introductionmentioning
confidence: 99%